WHAT DO STATE-OWNED DEVELOPMENT FINANCIAL INSTITUTIONS (SODFIS) IN SOUTH AFRICA DO? - Adebayo, Adeyemi (Economic Annals, 2022)
This study explores the model of state-owned development financial institutions (SODFIs) in South Africa and how South African SODFIs contribute to national, continental, and international developmental agendas by providing necessary support towards financing domestic and international projects, thereby mitigating seven categories of market failures. It analyses relevant documents and the latest annual/integrated reports of the SODFIs, making it possible to highlight their modus operandi and the instruments employed in fulfilling their mandates. Analyses indicate that although SODFIs in South Africa mitigate market failures by adequately contributing to national, continental, and global developmental agendas, they do not fund state-owned enterprises (SOEs), leaving out an important aspect of public socioeconomic cooperation. This study thus highlights the importance of funding SOEs partly through SODFIs rather than directly from the national budget and discusses implications for theory and practice.